2015
DOI: 10.1007/s40618-015-0259-x
|View full text |Cite
|
Sign up to set email alerts
|

Embolization of left spermatic vein in non-obstructive azoospermic men with varicocele: role of FSH to predict the appearance of ejaculated spermatozoa after treatment

Abstract: Selected patients with NOA may show ejaculated spermatozoa after a non-invasive repair of a left side varicocele, therefore avoiding testicular sperm extraction. Baseline serum FSH was a valuable predictor for ejaculated spermatozoa after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The current study observed that testicular volume was not predictive of post‐varicocelectomy sperm recovery in the ejaculate, in agreement with others (Abdel‐Meguid, ; Aboutaleb et al, ; Cakan & Altug, ; D'Andrea et al, ; Esteves & Glina, ; Ishikawa, Kondo, Yamaguchi, Sakamoto, & Fujisawa, ; Pasqualotto et al, ; Youssef et al, ). Similarly, we found no significant association between any of the reproductive hormones (FSH, LH, testosterone, oestradiol) and sperm recovery in the ejaculate post‐varicocelectomy, in agreement with most studies in the review.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The current study observed that testicular volume was not predictive of post‐varicocelectomy sperm recovery in the ejaculate, in agreement with others (Abdel‐Meguid, ; Aboutaleb et al, ; Cakan & Altug, ; D'Andrea et al, ; Esteves & Glina, ; Ishikawa, Kondo, Yamaguchi, Sakamoto, & Fujisawa, ; Pasqualotto et al, ; Youssef et al, ). Similarly, we found no significant association between any of the reproductive hormones (FSH, LH, testosterone, oestradiol) and sperm recovery in the ejaculate post‐varicocelectomy, in agreement with most studies in the review.…”
Section: Discussionsupporting
confidence: 92%
“…However, another seven studies had a higher sperm recovery rate (range 43%–56%; Esteves & Glina, ; Gat, Bachar, Everaert, Levinger, & Gornish, ; Haydardedeoglu et al, ; Kim et al, ; Matthews et al, ; Poulakis, Ferakis, Vries, Witzsch, & Becht, ; Zampieri et al, ). The higher sperm recovery rate of these seven studies could probably be due to (a) their small sample sizes (mean 24 patients) compared with the remaining studies (mean 39 patients) and (b) the possibility that these seven studies had more favourable testicular histopathologies leading to higher sperm recovery rate, as most of them did not report the histopathology (D'Andrea et al, ; Gat et al, ; Matthews et al, ; Poulakis et al, ; Zampieri et al, ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Eleven retrospective and seven prospective studies were included in this systematic review and accounted for 468 treated patients who had complete azoospermia and were subjected to either surgical varicocele repair or percutaneous embolization. 6 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 In 13 of the included studies, patients were subjected to varicocele repair using either inguinal or subinguinal microsurgical methods. 6 14 15 16 17 19 22 23 24 25 26 27 30 In one 29 and three studies, 18 20 28 respectively, inguinal macroscopic varicocelectomy and anterograde or retrograde percutaneous embolization were the treatment methods.…”
Section: Resultsmentioning
confidence: 99%
“…Gray-scale sonograms allow the accurate assessment of testicular volume and texture, the evaluation of epididymis size and texture and the detection of enlargements in the pampiniform venous plexus [ 11 , 12 ]. When combined with colour Doppler spectrum analysis, US also provides a quantitative measure of spermatic venous reflux in patients with clinical varicocele [ 24 , 25 ] and can identify subclinical varicocele or assist in the follow-up of varicocele repair [ 26 ]. Of note, infertile oligozoospermic men exhibit an increased risk of testicular germ cell tumour (TGCT) compared with fertile control subjects [ 27 ] and, in infertile men, the presence of testicular microlithiasis is associated to an about 18-fold higher prevalence of testicular cancer [ 28 ], thus further supporting the recommendation to perform scrotal US in all infertile men with OAT [ 14 ].…”
Section: Diagnostic Work Up Of Men From the Infertile Couplementioning
confidence: 99%